The over-expression of cell migratory genes in alveolar rhabdomyosarcoma could contribute to metastatic spread - Rapa, E; Hill, S; Morten, K; Potter, M; Mitchell, C (2012)
Alveolar (ARMS) and Embryonal (ERMS) rhabdomyosarcoma differ in their response to current treatments. The ARMS subtype has a less favourable prognosis and often presents with widespread metastases, while the less metastatic ERMS has a 5 year survival rate of more than 80 %. In this study we investigate gene expression differences that could contribute to the high frequency of metastasis in ARMS. Microarray analysis identified significant differences in DNA repair, cell cycle and cell migration between the two RMS subtypes. Two genes up regulated in ARMS and involved in cell migration; the engulfment and cell motility gene 1 (ELMO1) and NEL-like 1 gene (NELL1) were selected for further nvestigation. Over-expression of ELMO1 significantly increased cell invasion from 24.70 ± 7 % to 93 ± 5.4 % in primary myoblasts and from 29.43 ± 2.1 % to 87.33 ± 4.1 % in the ERMS cell line RD. siRNA knockout of ELMO1 in the ARMS cell line RH30 significantly reduced cell invasion from 88.2 ± 3.8 % to 35.2 ± 2.5 %. Over-expression of NELL1 significantly increased myoblast invasion from 23.6 ± 6.9 % to 100 ± 0.1 %, but had no effect on invasion of the ERMS cell line RD. These findings suggest that ELMO1 may play a key role in ARMS metastasis. NELL1 increased invasion in primary myoblasts, but other factors required for it to enhance motility were not present in the RD ERMS cell line. Impairing ELMO1 function by pharmacological or siRNA knockdown could be a highly effective approach to reduce the metastatic spread of RMS. © Springer Science+Business Media B.V. 2012.